Molecular docking studies of selected natural compounds as caspase-3 enzyme inhibitors / Wan Dalila Wan Chik and Zafirah Liyana Abdullah - Wan Chik, Wan Dalila; Abdullah, Zafirah Liyana (Universiti Teknologi MARA, Pulau Pinang, 2022)
Caspase-3 plays a role in necrosis, apoptosis, and inflammation activities. Many studies have shown that caspase-3 expression and cancer are closely related. The regulatory mechanism performs their catalytic activities to promote their aggregation into dimers or macromolecular complexes. Thus, the mechanism's loss of function and insufficient caspase activation may result in tumour formation due to apoptosis malfunction. Therefore, it is essential to recognise small molecules that modulate caspase to facilitate treatment for apoptosis-related and inflammatory diseases. This work aimed to study the molecular interaction of selected natural compounds with inhibitory activities towards caspase-3 by molecular docking approaches. The docking was performed onto caspase-3 with the potential compounds using Autodock Vina. Our results demonstrated that the 1-methyl-5-(2-phenoxymethyl-pyrrolidine-1-sulfonyl) - 1H-indole-2, 3-dione (PDB ID: 1GFW), and B92 (PDB ID: 3KJF) were found to be the best potent inhibitors of caspase-3 with the binding energy of -8.4 Kcal/mol and -8.3 Kcal/mol, respectively. Hydrogen bond formations in the caspase-3 complex were found through T62, H121, G122, S205, R207, N208, and W214 residues. The potential inhibitory activities of these compounds may be further validated through in vitro and in vivo studies in future works.